Support over Safety? Rethinking How Organizational Support Empowers Gen Z in The Workplace - Gita Widya Laksmini Soerjoatmodjo (Program Studi Psikologi UIN Sunan Ampel Surabaya, 2025)
This study aims to examine the relationship between perceived organizational support (POS), psychological safety climate (PSC), and psychological empowerment (PE) among Generation Z employees. While previous literature emphasizes the importance of team-based psychological safety in fostering empowerment, this study investigates whether organizational-level support may play a more dominant role for Gen Z workers. A cross-sectional quantitative design was used, involving 403 Gen Z employees from various sectors in Indonesia. Data were collected through self-report questionnaires and analyzed using structural equation modeling in JASP. The results revealed that POS had a strong and significant direct effect on PE (β = 0.518, p < .001). POS also significantly predicted PSC (β = 0.586, p < .001), but the mediating role of PSC was not supported, as the path from PSC to PE was not statistically significant (β = 0.114, p = .054). These findings suggest that Gen Z employees are more empowered by structural support and responsive leadership than by psychological safety within team interactions. The study contributes to the evolving understanding of Gen Z in the workplace and offers practical implications for designing more effective empowerment strategies.